Understanding and Establishing Appropriate Behaviours for Effective Asset Management - Booker, Nigel (Technium Business and Management, 2025)
Taking cognitive psychology into account when developing asset management policy and procedures represents innovative and transformative approach. Industry sector feedback suggests that such considerations are highly significant to the effectiveness and sustainment of good asset management practices. The incorporation of psychology promotes creative thinking, operates cross-functionally, is industry-agnostic, and actively encourages diversity of thought. This innovative intersection of psychology and asset management is gaining recognition for its potential to bring fresh perspectives and enhance overall effectiveness.